The Effect of Conservative Oxygen Therapy in Reducing Mortality in Critical Care Patients: A Meta-Analysis and Trial Sequential Analysis - Ni, Yue-Nan; Wang, Ting; Liang, Bin-Miao; Liang, Zong-An (Frontiers in Medicine, 2021)
Background Conservative oxygen therapy can prevent both hypoxemia and hyperoxemia, but the effect on the prognosis of patients admitted to the intensive care unit (ICU) remains controversial. Methods All controlled studies comparing conservative oxygen therapy and conventional oxygen therapy in adult patients admitted to the ICU were searched. The primary outcome was mortality, and the secondary outcomes were length of ICU stay (ICU LOS), length of hospital stay (hospital LOS), length of mechanical ventilation (MV) hours, new organ failure during ICU stay, and new infections during ICU stay. Results Nine trials with a total of 5759 patients were pooled in our final studies. Compared with conventional oxygen therapy, conservative oxygen therapy did not reduce overall mortality (Z=0.31, p=0.75) or ICU LOS (Z=0.17, p=0.86), with firm evidence from trial sequential analysis, or hospital LOS (Z=1.98, p=0.05) or new infections during the ICU stay (Z=1.45, p=0.15). However, conservative oxygen therapy was associated with a shorter MV time (Z=5.05, p<0.00001), reduction of new organ failure during the ICU stay (Z=2.05, p=0.04) and lower risk of renal replacement therapy (RRT) (Z=2.41, p=0.02). Conclusions Conservative oxygen therapy did not reduce mortality but did decrease MV time, new organ failure and risk of RRT in critically ill patients.